Interview for enrollment into the Bachelor of Pharmacy Program (PH240) / Syahida Fathiah Ahmad Kamal and Assoc. Prof. Dr. Mahmathi Karuppannan - Ahmad Kamal, Syahida Fathiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
A total of 905 eligible candidates have been called for interviews for admission to the Bachelor of Pharmacy (PH240) program in October 2023, with an expected enrollment of 180 students. Several meetings were held with the Student Recruitment Interview Committee, chaired by the Dean, to organize the interview process in the best possible way, considering the higher number of candidates compared to the previous years. Candidates from Sabah and Sarawak were interviewed via online platform on June 8, 2023, involving a total of 72 candidates, while the rest attended face-to-face interviews on June 10 and 11, 2023. The breakdown of the session on the interview date was communicated to the candidates via email and Telegram, ensuring minimal waiting time and organised crowd control. The interviews were divided into several stations, which included 4 active stations (Motivation, Communication, Ethics and Critical Thinking) and 2 rest stations (where candidates listened to music). Each circuit involved 6 candidates and lasted for 42 minutes. Given the large number of candidates, 3 Examination Halls with 3 circuits each were used.